Enhancing Critical Thinking Through Calla In Developing Writing Ability Of EFL Students - Yufrizal, Hery (Advances in Social Sciences Research Journal, 2019)
The objectives of this research are firstly to investigate the application of Cognitive Academic Language Learning Approach in improving students’ English writing ability andsecondly to answer what factors influence the students’ writing performance. The subjects of the research were the students of senior high schools in Indonesia consisting of a group of students as experimental group and as control group. The results showed that students improved their writing after they were involved in Cognitive Academic Language Learning Actvitities. Furthermore, the study also showed that levels of students’ critical thinking did not any significant effects toward their writing achievement